Wine, grapes, autochthonous grape varieties, foamy and sparkling properties, yeast, descriptors, phenolic substances, organic acids, aroma, taste - Olga N. Sheludko; https://orcid.org/0000-0001-8655-3375; Larisa E. Chemisova; Roman N. Bakhmetov (Техника и технология пищевых производств)
Table grapes that have lost their marketable appearance are considered waste products. However, such grapes still possess some technological properties that make it possible to use them as a raw material for wine and grape spirits. This research featured the effect of the composition and technology of table grape alcohols on the volatile compounds and sensory profile of grape beverages. The study involved six white and six red grape beverages. In the test samples, the fermentation process was stopped by adding wine spirits and grape spirits obtained by rectification of distillates from table grapes. In the control samples, the procedure involved rectified grain alcohol. The physicochemical parameters of drinks and spirits were defined by standard methods. The highly volatile compounds were determined by gas chromatography. The sensory assessment was conducted by panelists from the Winemaking Research Center of the North-Caucasian Federal Scientific Center of Horticulture, Viticulture, and Winemaking. In this study, the wine spirits and the grape spirits obtained from table grapes had no effect on the standard indicators, e.g., volatile acids and acetoin. However, they increased the mass concentrations of highly volatile compounds in the following manner: drinks with grain alcohol ˂ drinks with wine alcohol ˂ drinks with grape alcohol. The content of acetaldehyde increased by 10–14% while the contents of ethyl acetate, esters, and higher alcohols increased by 25–35, 4.5–8.5, and 15%, respectively. The furfural content increased by 0.4–1.4 mg/L in the samples with grape alcohol. The samples with white grape varieties acquired a more prominent floral-honey flavor whereas those with black grapes acquired hints of hazelnut and honey. As a result of the study, it was found that wine alcohol and grape alcohol moderately increased the content of volatile compounds in drinks and had a positive effect on their sensory perception, which proves the expediency of their use in beverage technology.